Utilization and quality of primary and specialized palliative homecare in nursing home residents vs. community dwellers: a claims data analysis - Poeck, Juliane; Meissner, Franziska; Ditscheid, Bianka; Krause, Markus; Wedding, Ulrich; Gebel, Cordula; Marschall, Ursula; Meyer, Gabriele; Schneider, Werner; Freytag, Antje (BMC palliative care, 2025)
Background There are hardly any data on the extent to which nursing home residents are provided with palliative homecare. We want to add evidence by comparing nursing home residents (who had been living in a nursing home for at least one year) and nursing-care-dependent community dwellers in terms of utilization and quality of palliative homecare. Methods We conducted a population-based study with nationwide claims data from deceased beneficiaries of a large German health insurance provider. First, we compared utilization rates of primary palliative care [PPC], specialized palliative homecare [SPHC], and no palliative care [noPC] between nursing home residents and community dwellers, both descriptively and adjusted for covariates. Second, we analyzed the (adjusted) relationship between PPC-only and SPHC (both: starting ≥ 30 days before death), and noPC with healthcare indicators (death in hospital, hospitalization, emergencies, intensive care treatment within the last 30 days of life), and compared these relationships between nursing home residents and community dwellers. Analyses were conducted using simple and multiple logistic regression. Data were standardized by age and gender. Results From 117,436 decedents in 2019, 71,803‬ could be included in the first, 55,367‬ in the second analysis. The rate of decedents with noPC was higher in nursing home residents (61.3%) compared to community dwellers (56.6%). Nursing home residents received less SPHC (10.7% vs. 23.2%) but more PPC (30.3% vs. 27.0%) than community dwellers, and achieved better outcomes across all end-of-life healthcare indicators. Adjusted for covariates, both types of palliative homecare were associated with beneficial outcomes, in nursing home residents as well as in community dwellers, with generally better outcomes for SPHC than PPC-only. For most outcomes, the associations with palliative homecare were equal or smaller in nursing home residents than in community dwellers. Conclusions The overall better performance in quality of end-of-life care in nursing home residents than in community dwellers may be due to the institutionally provided nursing and general practitioner care within nursing homes. This may also explain higher rates of PPC and lower rates of SPHC in nursing home residents, and why the relationship with both PPC and SPHC are smaller in nursing home residents. Trial registration German Clinical Trials Register (DRKS): [DRKS00024133, Date of registration: 28.06.2021].